Cellular photo(geno)toxicity of gefitinib after biotransformation - El Ouardi, Meryem; Tamarit, Lorena; Vayá, Ignacio; Miranda, Miguel A.; Andreu, Inmaculada (Frontiers in Pharmacology, 2023)
Gefitinib (GFT) is a selective EGFR inhibitor clinically used for the treatment of patients with non-small cell lung cancer. Bioactivation by mainly Phase I hepatic metabolism leads to chemically reactive metabolites such as O-Demethyl gefitinib (DMT-GFT), 4-Defluoro-4-hydroxy gefitinib (DF-GFT), and O-Demorpholinopropyl gefitinib (DMOR-GFT), which display an enhanced UV-light absorption. In this context, the aim of the present study is to investigate the capability of GFT metabolites to induce photosensitivity disorders and to elucidate the involved mechanisms. According to the neutral red uptake test, only DF-GFT metabolite can be considered non-phototoxic to cells. Moreover, DMOR-GFT is markedly more phototoxic than the parent drug, whereas DMT-GFT is much less phototoxic. Regarding thiobarbituric acid reactive substances formation, as an indicator of lipid oxidation, only DMOR-GFT is capable to photosensitize this process. Protein photooxidation (monitored by carbonyl content measurement) is mainly mediated by GFT and, to a lesser extent, by DMOR-GFT; in contrast, protein oxidation associated with DMT-GFT is nearly negligible. Interestingly, the damage to cellular DNA as revealed by the comet assay, indicates that DMT-GFT has the highest photogenotoxic potential; moreover, the DNA damage induced by this metabolite is hardly repaired by the cells after several hours. This could ultimately result in mutagenic and carcinogenic effects. These results could aid oncologists when prescribing TKIs to cancer patients and, thus, establish the conditions of use and recommend photoprotection guidelines.